Telecom cloud solution in re-architecture of MAN - Ding CHEN; Tao ZHANG; Ke LIU; Qiang LAN (Dianxin kexue)
Evolving the legacy network to SDN/NFV network is the strategy of carrier network re-architecture.Based on large-scale cases,multi-tier data centers architecture,application-driven telecom cloud infrastructure,vBRAS pool and C-U separation solutions were proposed.Session-consumed services and IPTV are the first several services that can be implemented by the new solution in MAN.And in those usecases,the carriers’ operators really combine the IT and CT operation teams into one virtual team,and push the evolution gradually.